Airport Passenger Terminal in Buleleng, Bali Circulation Pattern in The Design Of Airport Passenger Terminals in Buleleng - Suwanda, Danton; -, Widiastuti; Mudra, I Ketut (Journal of A Sustainable Global South; Vol 2 No 1 (2018): February 2018, 2020)
The transportation system is experiencing rapid development. One of the transportation systems that has developed qiote rapidly and is in great demand now is the air transportation system. The air transportation system is the main choice because air transportation can save the travel time when the distance is far enough. Development of time and technology, the increasing demand for air transportation has caused a lack of capacity at Bali’s airport. It is necessary to design a facility that can provide a place for air accommodation to accommodate the needs of air transportation users. Circulation is one thing that must be considered when designing an airport passenger terminal. Circulation are usually formed from a pattern of spatial structure so the circulation in the building will determine the smooth activity in the build- ing. Index Terms — transportation, circulation, terminal.